Hosoya Polynomials of Generalized Vertex Identified and Edge Introducing Graphs - Ahmed Ali; Noor Dahash (Al-Rafidain Journal of Computer Sciences and Mathematics)
The vertex identified and edge introducing graphs of two disjoint connected graphs are extended to n, , disjoint connected graphs. Hosoya polynomials and Wiener indices of such composite graphs are obtained by applying Gutman's Theorem and using mathematical induction on n.